74m² - Castillo, Paola; Panizza Montanari, Tiziana (Colectivo La Tribu : Errante Producciones, 2012)
"74 square meters is a documentary that portrays the journey of the leaders of 150 families in Valparaíso to get their own house. The team led by the management of Tiziana Panizza and Paola Castillo accompanied these women for 7 years, addressing the issue of social integration in the new neighborhood, the divisions in the community and the disasters caused by the rains in the new homes. A struggle for the house itself that is repeated throughout Chile"--